Theoretical and conceptual frame work for factors that lead to poor performance for learners with hearing impairment in the national examination at grade nine (9): A case of ChilesheChepela Special School and Musakanya Special Unit in Kasama and Mpika district - Mwansa Mbulo; Penda Annie (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
This manuscript is an extract of a theoretical framework and conceptual framework from a Master’s an on-going study onfactors that lead to poor performance for learners with hearing impairment in the national examination at grade nine (9): A case of Chileshe Chepela Special School and Musakanya Special Unit in Kasama and Mpika district. The work is an attempt to identify the factors affecting learners with hearing impairment in the national examination at Chileshe Chepela Special School and Musakanya Special Unit in Kasama and Mpika district in Zambia. Among the factors that can affect these learners during the national examinations are such as identification of learners’ relevant predispositions, specification of appropriate objectives and sequence, utilization of appropriate instruction procedure, assessment of learner’s performance. It is argued that if these factors are identified and implemented learners with hearing impairment can benefit a lot from national examination through obtaining better grades.